Implementasi LIMIT ’25 untuk Pembinaan Prestasi dan Daya Saing Matematika Siswa SMA Gorontalo - Hikmahturrahman; Zulfahmi Mustapa R; Suhardiman Darson Tamu; Febiyanti R. Hasan; Rizal Masaniku; Rahmi Nindi Arsyad; Maulidina Basalama; Nur’ain S. Patilima; Nur Elina Karim; Nursakiah (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Low student interest and achievement in mathematics remain important educational issues that require attention in Gorontalo Province. This condition calls for a development program that is not only competition-oriented but also capable of fostering learning motivation, self-confidence, competitiveness, critical thinking skills, and problem-solving abilities. This community service activity was implemented through the 2025 Mathematics Scientific League (LIMIT ’25) as a platform for developing the academic potential of senior high school students across Gorontalo Province. The purpose of this activity was to provide an educational, healthy, collaborative, and inspiring mathematics competition for students while strengthening networks among schools, teachers, university students, and higher education institutions. The implementation method used a community-based participatory action approach consisting of socialization, participant registration, technical preparation, competition implementation, evaluation, and reflection. This activity involved lecturers and university students as organizers, mathematics teachers as mentors, and students as the main participants. LIMIT ’25 was attended by 34 teams or 68 students from six regencies/cities in Gorontalo Province. Based on the implementation results, observations, evaluations, and participant reflections, this activity encouraged active student participation, increased positive competitive spirit, strengthened teamwork, and provided a challenging and meaningful mathematics learning experience. Participants also had the opportunity to test their conceptual understanding, reasoning strategies, and decision-making accuracy in solving non-routine problems. In addition, this activity created a space for communication among senior high school mathematics teachers in supporting sustainable student achievement development. This program can also be replicated as an annual agenda to expand the impact of regional mathematics development. Thus, LIMIT ’25 demonstrates its potential as a medium for mathematics achievement development, numeracy literacy strengthening, and community-based educational ecosystem development in Gorontalo through sustainable collaboration between universities and schools